Technical Challenges of Molecular-Imprinting-Based Optical Sensors for Environmental Pollutants - Arabi, Maryam; Chen, Lingxin (Langmuir, 2022)
Combating environmental pollution constantly requires new affinity tools to selectively recognize and sensitively detect them. Molecularly imprinted polymers (MIPs) are plastic antibodies that have exhibited great potential as recognition units in optical sensing platforms to monitor wide varieties of environmental pollutants, including ionic species, organic compounds, gases, and even manufactured nanoparticles. The construction, sensing strategies, and applications of molecular-imprinting-based optical sensors (MI-OSs) have been discussed in recent reviews, thus we deliberately set them aside. This Perspective elaborates on unanswered questions and main approaches being taken to address the challenges of MI-OS technologies, which have been less considered until now. Specifically, we highlight obscure technical aspects of MI-OS fabrication and validation that impact their practical applications and importantly offer conceivable solutions to related problems to bridge the research gap.